Project VeSElkA: results of abundance analysis I – HD 71030, HD 95608, HD 116235 and HD 186568. Issue 4 (10th September 2015) - LeBlanc, F.; Khalack, V.; Yameogo, B.; Thibeault, C.; Gallant, I.
Abstract: A portion of main-sequence stars, called chemically peculiar (CP) stars, show important abundance anomalies mainly due to atomic diffusion of the species within these stars. Certain CP stars have hydrodynamically stable atmospheres where atomic diffusion may dominate and lead to vertical abundance stratification there. Recently, Project VeSElkA (a word meaning rainbow in Ukrainian and standing for 'Vertical Stratification of Element Abundances') was initiated with the goal to detect vertical stratification of chemical abundances in selected CP stars using high-resolution spectra with large signal-to-noise ratios. The first extensive and detailed series of results from atomic-line analysis is presented here for four stars of Project VeSElkA: HD 71030, HD 95608, HD 116235 and HD 186568. These stars were recently observed with ESPaDOnS at Canada–France–Hawaii Telescope. Strong evidence of iron stratification in the atmospheres of HD 95608 and HD 116235 was found. Chromium also shows a steep abundance gradient in the upper atmospheres of these two stars. No evidence of stratification is found for HD 71030 and HD 186568.